2019
DOI: 10.1016/j.chembiol.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Design on a Rational Basis of High-Affinity Peptides Inhibiting the Histone Chaperone ASF1

Abstract: Highlights d Development of a computational pipeline for the design of high-affinity peptides d Epitope tethering and contacts optimization lead to nanomolar ASF1-binding peptides d The optimal peptide inhibited cell proliferation and perturbed cell cycle d Injected in mouse allografts, it reduced tumor growth and induced apoptosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…In our previous study, we showed that Trp3 combined with the ASTE motif led to a 10-fold increase in the affinity for ASF1. (30) With the aim to further improve apolar contacts with the surface of ASF1, we substituted Trp3 in P3 by a napthylalanine (Nal3 in P4) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we showed that Trp3 combined with the ASTE motif led to a 10-fold increase in the affinity for ASF1. (30) With the aim to further improve apolar contacts with the surface of ASF1, we substituted Trp3 in P3 by a napthylalanine (Nal3 in P4) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…2). The binding affinity remained in the (C) Structure of the complex hASF1A(1-156)-ip4 (pdb 6foh) (30). same range as that of P3, but the analysis of the thermodynamic parameters indicated a more favorable contribution to binding entropy (Table 1 and fig.…”
Section: Defining the Minimal Helical Part Required For Asf1 Bindingmentioning
confidence: 96%
“…As in ip4, peptides P1 to P3 contain a Trp in position 3 whose indole side chain enables favorable interactions with the apolar patch in ASF1 formed by Val 92 and Tyr 112 . In our previous study, we showed that Trp 3 combined with the N-terminal capping motif led to a 10-fold increase in the affinity for ASF1 (30). With the aim to further improve apolar contacts with the surface of ASF1, we substituted Trp 3 in P3 by a napthylalanine (Nal 3 in P4) (Fig.…”
Section: Defining the Minimal Helical Part Required For Asf1 Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…( 30) Upon conjugation to a cell-penetrating peptide (CPP), ip4 was able to translocate into cells, impair cell proliferation and perturb the cell cycle progression similarly to the silencing of ASF1. (30) Injection of this conjugate in mouse allografts reduced tumor growth. However, further exploration of its therapeutic potential was early compromised by its sensitivity to protease degradation.…”
Section: Introductionmentioning
confidence: 99%